Penyalahgunaan Wewenang Oleh Aparatur Negara Dalam Pembangunan Gedung DPRD Kota Batam - Rina Shahriyani Shahrullah; Asmin Patros; Rional Putra (Fakultas Hukum, Universitas Internasional Batam, 2014)
In the background of this thesis the researcher raised about the problem of abuse of authority of Batam City Government officials in the procurement of goods and services Batam City Council Building. In other research problems are discussions about the case of abuse of authority officials in the construction of the Parliament building in Batam. As well as indications of Corruption in Procurement Building Project Batam City Council were not followed up. This type of research conducted by the sociological juridical approach to the analysis of data using qualitative data. Sociological juridical approach aims to describe systematically and accurately about the population or about a particular field as well as trying to describe a situation or event on the reality on the ground against the perpetrators of corruption committed by government officials in Batam. In terms of addressing the corruption problem procurement of goods and services, is actually not a problem that only the responsibility of the government and a group of institutions or certain people, but also an obligation of the community to cope. Patterns of fighting corruption at the community level can be done through monitoring, reporting, dissemination of information and knowledge and other patterns. This effort is actually in the interests of the nation and the State of Indonesia, especially in improving the image and confidence International.